Diagnosing Rickettsia felis infection with Metagenomic Next-Generation Sequencing (mNGS) in a patient with ankylosing spondylitis: a case report and literature review - Liu, Mengyao; Cheng, Yang; Wang, Xinchang; He, Zhaochun; Yang, Kepeng; Chen, Kai; Fan, Yongsheng; Wang, Weijie (Frontiers in Immunology, 2025)
Rickettsia felis, an emerging flea-borne pathogen with global distribution potential, is a neglected cause of undifferentiated febrile illness, although reported human cases remain sparse. The development of molecular diagnostic methods, along with the application of metagenomic next-generation sequencing (mNGS), has improved the diagnostic accuracy of infectious fevers. A case of Rickettsia felis infection was diagnosed by mNGS in a 55-year-old patient with pre-existing ankylosing spondylitis. Five previously reported cases of Rickettsia felis infection were systematically reviewed, with a comprehensive analysis of their epidemiological characteristics, clinical manifestations, and therapeutic regimens. This study highlights the clinical features and diagnostic approaches of the disease through a case report and literature review.